A treatise on mystical love - Daylamī, Abū al-Ḥasan ʻAlī ibn Muḥammad, active 1000 (Journal of Arabic and Islamic studies. Monograph series, 2005)
The earliest major Islamic treatise on mystical love, this work reflects a moderate version of the ecstatic mysticism of the Sufi martyr al-Hallaj.